The consequences of intrapreneurship in exporting firms: a structural-model approach - Brás, Gonçalo Nuno Rodrigues (2021)
A number of recent scientific articles have studied the relationship between entrepreneurial orientation (EO) and firm’s performance, though not all came in the scope of international entrepreneurship (IE). Researchers often test mediating or moderating variables that help explain this relationship. The extensive academic findings lead us to a wide range of mediating/moderating variables and to a lack of consensus in this domain. This study is in scope of IE literature, and it aims to provide new and robust insights supported by consistent empirical findings and to adopt this structural-model approach as a reference in the absence of academic consensus. Specifically, the paper examines the contribution of intrapreneurship to both the firm’s international orientation (IO) and performance in light of the IE guidelines. To this end, we examine how the EO of Portuguese exporters influences corporate performance taking into account the meditating effect of their IO on the EO –performance association through structural equation modelling. Results confirm that IO positively and significantly mediates the relationship between EO and corporate performance. EO and IO were also found to have a direct and positive effect on corporate performance. These findings confirm the relevance of intrapreneurship and international commitment to a better organisational performance and gives us empirical support to conclude that effort taken in these domains could enhance the exporters’ performance. Moreover, this study makes an empirical and theoretical contribution to the IE topic and therefore aims to be a reference to the literature in this domain.